Structural basis for MTA1c-mediated DNA N6-adenine methylation - Jiyun Chen; Rong Hu; Ying Chen; Xiaofeng Lin; Wenwen Xiang; Hong Chen; Canglin Yao; Liang Liu (Nature Communications, 2022)
DNA N6-adenine methylation (6 mA) plays a crucial role in epigenetic regulation in eukaryotes. Here, the authors determined nine crystal structures of the ciliates 6 mA methyltransferase complexes, providing the molecular basis for understanding the functions of 6 mA.